THE UTILITIZATION OF VIRAL ENGLISH SONGS THROUGH SPOTIFY TO IMPROVE STUDENTS LISTENING SKILL : STUDENTS’ EXPERIENCE - Rezi, Firman Alfa; Destia, Destia; Wahyudi, Rizki; Elentiranda, Chesa; Fikri, Mhd Ahlul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to determine the potential benefits of viral English songs on Spotify in improving skills based on students' experiences. Using a quantitative approach, this study used a questionnaire through statements of the advantages and disadvantages of viral English songs on Spotify in improving English listening skills with 5th semester English education students from the University of Muhammadiyah Riau using purposive sampling with a sample size of 30 students. The results of the study showed 20 valid questions and a Cronbach alpha value of 0.889 which showed high reliability and produced positive responses from students who concluded that utilizing viral English songs could improve their English listening skills. Based on the findings of the study, it shows that viral English songs on Spotify are very important in improving students' English listening skills. Because viral English songs on Spotify have high-level vocabulary and various pronunciations that are equivalent to native English speakers which can help students face exams and the future that require English in a fun way.